KIẾN THỨC PHÒNG NGỪA BIẾN CHỨNG TĂNG HUYẾT ÁP CỦA NGƯỜI CAO TUỔI TẠI XÃ NGỌC SƠN THÀNH PHỐ HẢI DƯƠNG NĂM 2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge regarding the prevention of hypertension complications among elderly individuals with hypertension in Ngoc Son commune, Hai Duong city, in 2023.Method: A cross-sectional study was conducted on 240 elderly individuals diagnosed with hypertension in Ngoc Son commune, Hai Duong city, in 2023.Results: Among the study participants, 60% were female and 40% were male, with a mean age is 63 years old. The majority were farmers (45%). The study revealed that 11.7% of participants had good knowledge, 61.7% had moderate knowledge, and 26.7% had poor knowledge regarding measures to prevent hypertension complications. Most participants were aware that reducing salt intake (56.7%), increasing consumption of green vegetables (56.7%), limiting animal fat (43.3%), reducing alcohol consumption (68.3%), and engaging in regular physical activity (55%) are important preventive strategies. However, only 16.7% recognized the importance of avoiding overweight and obesity, 35% acknowledged the necessity of quitting smoking, and 21.7% were aware of the need to avoid sudden temperature changes.Conclusion: The study revealed that only 11.7% of participants possessed good knowledge, while the majority had moderate (61.7%) or poor (26.7%) knowledge of preventive measures for hypertension complications. Most participants were familiar with basic preventive practices, such as salt intake, increasing vegetable intake, and engaging in regular exercise; however, significant gaps remained in more comprehensive and specific knowledge.
Keywords: elderly, knowledge, prevention of hypertension complications.